DAMPAK KONFLIK DI LAUT CHINA SELATAN TERHADAP STABILITAS KAWASAN ASIA TENGGARA - Kevin Andreas Halomoan Tambunan; Ridha Nababan; Rimma Anisa Siagian; Roslin Naiborhu; Sintia Harianti; Prayetno (STKIP Subang, 2025)
The conflict in the South China Sea involves overlapping claims between six countries, namely China, the Philippines, Taiwan, Brunei, Malaysia and Vietnam. The main cause of this conflict is the potential for abundant natural resources, including oil and gas, as well as strategic international trade routes. China claims almost the entire region through the decree line, sparking tensions and protests from other countries. The purpose of this paper is to examine the impact of the conflict in the South China Sea on stability in the Southeast Asia region. This research uses the literature study method. This type of method is collecting data by searching for sources and constructing them from various sources such as books, journals and research that has already been carried out. Literature study is an effort carried out by researchers to collect information that is relevant to the topic or problem that will be or is being researched. So, based on this research to determine the impact of this conflict on the stability of Southeast Asia includes increasing military tensions and economic challenges for the countries involved.